A student participation assessment scheme for effective teaching and learning. Issue 1 (1st June 2014) - Abuid, Bader Ahmed
Abstract : In this paper a systematic and well-defined student participation assessment scheme for college courses is proposed. The scheme supports the involvement of students in a variety of areas of participation within and outside the classroom with the aim of improving their learning. The scheme addresses mostly the challenges related to the practicality of the structure and design of the assessment. It also addresses the subjectivity of grading student participations. Areas of participation are widened to allow the faculty more accurate information about the conduct of each individual student towards more objective assessment. In addition, it provides the faculty with the flexibility to select areas that best fit the learning outcomes, nature of the course, availability of time and resources, and class atmosphere. The proposed scheme is initiated and developed using feedback from the teaching staff of Nizwa College of Technology, (NCT) through a survey and open discussion. The results indicate that over two thirds of the surveyed staff show agreement with the concept of assessing participation and find the scheme design clear and systematic, while 82% of them perceive the scheme as effective in improving the motivation and learning of students.